Formulation and phytochemical analysis of a potentially functional beverage from combining a leaf extract and pulp of Annona muricata (Annonaceae) - Yolanda Nolasco-González; María de Lourdes García-Magaña; Andrés Eloy León-Fernández; Juan L. Monribot-Villanueva; José A. Guerrero-Analco; Efigenia Montalvo González (Acta Botanica Mexicana)
Background and Aims: Annona muricata beverages are widely used in traditional medicine to treat different ailments; however, they have been little characterized phytochemically and are consumed as sugary beverages, and may contribute to non-communicable diseases, including obesity. The objective of this work was to obtain and characterize a sensorially acceptable beverage from an extract of A. muricata leaves and pulp.